Investigation of the Mediating Effect of Strategic Posture on the Relationship between Environmental Conditions and Firm Performance on the Logistics Sector - Saniye Yıldırım Özmutlu; Esin Can Mutlu (Istanbul Business Research)
The effects of environmental conditions on firm performance are investigated in this study. Within the scope of the research, the relationships between the strategic posture and the performance of logistics companies in varying environmental conditions were examined. During this study, the interaction between variables was also investigated by predicting the presence of the mediating effect of strategic posture. In this context, a research model and related research hypotheses were developed. The created research model was comprised of the three-dimension of environmental conditions developed by Dess and Beard (1984), six dimensions of strategic stance developed by Venkatraman (1989), and firm performance variables. A survey related to the research was conducted with 264 people working in managerial positions in 218 logistics companies operating within the scope of the research to test the hypotheses in the research model. The analysis of the obtained data was performed by the Structural Equation Modeling (SEM) method utilizing the SPSS and AMOS software program. According to the analysis results, it was determined that the strategic posture variable has a full mediating effect between environmental conditions and firm performance. As a result, by enabling logistics companies to realize their strategic posture features, information was provided to guide them on how to improve their performance in changing environmental conditions.